A study of the Academic Management of the Administrators of Achcharalai interdisciplinary School Nakhon Sawan Secondary Education Service Area according to Trisikkhã: - - Sornboonkied , Yanisa; Thuenchang, Worrakrit; Tasagri , Tanong (Mahachula Academic Journal, 2026)
The objectives of this research were to: (1) to study the academic administration of school administrators in the Acharalai School Consortium under the Nakhon Sawan Secondary Educational Service Area Office, and (2) to propose guidelines for developing the academic administration of school administrators in the Acharalai School Consortium based on the principles of the Threefold Training (Trisikkha). This study employed a mixed-methods research design. For the quantitative phase, the sample consisted of 226 teachers. The research instrument was a questionnaire, and the data were analyzed using frequency, percentage, and standard deviation. For the qualitative phase, eight key informants were selected, and data were collected using a semi-structured interview. The qualitative data were analyzed through content analysis. The findings of this research are expected to provide useful information and practical guidelines for improving academic administration in schools in accordance with the principles of Trisikkha, which emphasize moral development (Sila), mental development (Samadhi), and wisdom development (Panna), thereby contributing to more effective educational administration. The research findings revealed that: (1) The status of academic administration of school administrators in the Acharalai School Consortium under the Nakhon Sawan Secondary Educational Service Area Office was examined in five aspects. The findings indicated that administrators, deputy administrators, and teachers rated all items at the highest level. Specifically, administrators encouraged teachers to participate in the development of the school curriculum with a mean of 4.35 and a standard deviation of 0.64. Administrators also promoted learner-centered instructional management with a mean of 4.37 and a standard deviation of 0.61. In addition, administrators conducted supervision, monitoring, and continuous guidance for teachers with a mean of 4.38 and a standard deviation of 0.60. Administrators supported teachers to attend training and seminars continuously with a mean of 4.39 and a standard deviation of 0.59. The item with the lowest mean score, though still at the highest level, was administrators encouraging teachers to use a variety of assessment methods, with a mean of 4.36 and a standard deviation of 0.62. (2) The study of academic administration of school administrators in the Acharalai School Consortium under the Nakhon Sawan Secondary Educational Service Area Office based on the principles of the Threefold Training (Trisikkha) revealed guidelines for the development of academic administration. The findings indicated that there were 15 development guidelines across five aspects of academic administration. These guidelines were categorized according to the principles of Trisikkha, consisting of five guidelines related to moral discipline (Sila), five guidelines related to mental concentration (Samadhi), and five guidelines related to wisdom (Panna). The guidelines emphasize that school administrators should integrate ethical conduct, mental discipline, and wisdom into academic administration practices in order to enhance transparency, fairness, responsibility, and effectiveness in educational management. The application of the principles of Sila, Samadhi, and Panna contributes to the development of a systematic and sustainable approach to academic administration within schools.